2020
DOI: 10.3390/cancers12113376
|View full text |Cite
|
Sign up to set email alerts
|

IgE Activates Monocytes from Cancer Patients to Acquire a Pro-Inflammatory Phenotype

Abstract: IgE contributes to host-protective functions in parasitic and bacterial infections, often by monocyte and macrophage recruitment. We previously reported that monocytes contribute to tumour antigen-specific IgE-mediated tumour growth restriction in rodent models. Here, we investigate the impact of IgE stimulation on monocyte response, cellular signalling, secretory and tumour killing functions. IgE cross-linking on human monocytes with polyclonal antibodies to mimic formation of immune complexes induced upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…This can create localized immune cell activation and release of cytokines, histamine, and other tumor toxic factors which can prevent cancer growth and spread. These attributes of IgE and its ability to activate immune cells towards activated phenotypes and to restrict tumor growth have been investigated in several models of cancer by our group and others [109][110][111][112][113]. The MOv18 IgE trial has hailed the first-in-class IgE antibody, which is tested in a first-in-human phase I clinical trial at Guy's Hospital, London, and three other trial centers in the U.K.…”
Section: Basophil Activation Evaluated In the Bat As A Tool To Predict Propensity For Type 1 Hypersensitivity To Emerging Ige Immunotheramentioning
confidence: 99%
“…This can create localized immune cell activation and release of cytokines, histamine, and other tumor toxic factors which can prevent cancer growth and spread. These attributes of IgE and its ability to activate immune cells towards activated phenotypes and to restrict tumor growth have been investigated in several models of cancer by our group and others [109][110][111][112][113]. The MOv18 IgE trial has hailed the first-in-class IgE antibody, which is tested in a first-in-human phase I clinical trial at Guy's Hospital, London, and three other trial centers in the U.K.…”
Section: Basophil Activation Evaluated In the Bat As A Tool To Predict Propensity For Type 1 Hypersensitivity To Emerging Ige Immunotheramentioning
confidence: 99%
“…While a detailed investigation of the immunological mechanisms underlying the effects of anti-CSPG4 IgE was not the objective of the present study, it was previously demonstrated that IgE signaling could recruit and activate macrophages through a TNFα/MCP-1 pathway to adopt a pro-inflammatory, anti-tumoral phenotype, alongside triggering immune signaling pathways signifying parasite clearance rather than allergic response. 15 , 16 , 52 , 53 Importantly, we have shown that a human/mouse chimeric IgE did not cause basophil degranulation in blood samples from cancer patients, 34 , 54 and that the rat anti-CSPG4 IgE was shown to be safe in an immunocompetent rat model. 48 …”
Section: Discussionmentioning
confidence: 89%
“…The promising research on the role of IgE in cancer has led to the establishment of the emerging field of AllergoOncology, investigating multifaceted functions of IgE in cancer [27,28]. Interestingly, IgE may reprogram monocytes and macrophages toward cytotoxic functions, 7,41 and the first therapeutic application of tumor-specific IgE antibody MOv18 in ovarian cancer patients is presently ongoing in a registered clinical trial (NCT02546921). Overall, we provide evidence for a detrimental role of IgG4 in CRC from combined in vitro and patient-derived phenotypic and functional evaluations.…”
Section: Discussionmentioning
confidence: 99%